The Effect of Aromatherapy with Lavender on Pain of Needle Insertion and Severity of Restless Legs Syndrome in Hemodialysis Patients; a Systematic Review and Meta-analysis - Izadi, Fatemeh; Mazhari, Seyed Amirhossein; Najafi, Masoomeh; Ashoobi, Mohammad Taghi; Sarafi, Milad; Karkhah, Samad; Ghorbani Vajargah , Pooyan; Takasi, Poorya; Firooz , Mahbobeh; Hosseini , Seyed Javad; et al. (Archives of Academic Emergency Medicine, 2023)
Introduction: Pain experienced during the insertion of a catheter into the arteriovenous fistula (AVF) and restless legs syndrome (RLS) are prevalent issues among Hemodialysis (HD) patients. The primary objective of this systematic review and meta-analysis was to consolidate the findings from randomized clinical trial (RCT) studies examining the impact of aromatherapy with lavender on the pain associated with AVF catheter insertion and RLS in HD patients. Methods: A systematic search was conducted on PubMed, Web of Science, Scopus, Cochrane, Embase, ClinicalTrials.gov, and Google Scholar search engine from inception to August 1, 2022, using keywords extracted from Medical Subject Headings, such as “Aromatherapy”, “Lavender”, “Arteriovenous fistula”, “Pain”, “Restless legs syndrome”, and “Hemodialysis”. Results: Finally, eleven articles were included in this systematic review and meta-analysis. The results showed that aromatherapy reduced the average pain of catheter insertion in AVF compared to the control group (Standard Mean Difference: -1.60, 95% Confidence Interval: -2.32 to -0.87, Z=4.32, I2:90.3%, P<0.001). Also, aromatherapy massage reduced the average severity of RLS compared to the control group, which was statistically significant (Weighted Mean Difference: -13.21, 95% Confidence Interval: -17.50 to -8.91, Z=6.03, I2:93.0%, P<0.001). Also, the subgroup analysis showed that lavender in the intervention group significantly decreased the pain intensity compared to the "no intervention" group (P<0.001), yet it was not significant compared to the placebo group (P=0.12). Conclusion: In summary, the findings indicate a notable reduction in catheter insertion pain in AVF and relief from RLS among HD patients through the use of lavender essential oil. As a result, future research is encouraged to include a comparison of lavender’s effects with those of a placebo group.